2022
DOI: 10.3389/fpls.2022.967031
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated mutation in auxin efflux carrier OsPIN9 confers chilling tolerance by modulating reactive oxygen species homeostasis in rice

Abstract: Phytohormone auxin plays a vital role in plant development and responses to environmental stresses. The spatial and temporal distribution of auxin mainly relies on the polar distribution of the PIN-FORMED (PIN) auxin efflux carriers. In this study, we dissected the functions of OsPIN9, a monocot-specific auxin efflux carrier gene, in modulating chilling tolerance in rice. The results showed that OsPIN9 expression was dramatically and rapidly suppressed by chilling stress (4°C) in rice seedlings. The homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Recently, Manna et al (2022) [63] reported that salt and drought treatment significantly induced OsPIN9 expression, indicating the potential role of OsPIN9 in abiotic stress adaptation. In line with this, our previous study showed that mutation of OsPIN9 by CRISPR/Cas9 technology confers enhanced chilling tolerance in rice [64]. However, whether and how OsPIN9 overexpression regulates rice chilling tolerance is unknown.…”
Section: Introductionmentioning
confidence: 74%
“…Recently, Manna et al (2022) [63] reported that salt and drought treatment significantly induced OsPIN9 expression, indicating the potential role of OsPIN9 in abiotic stress adaptation. In line with this, our previous study showed that mutation of OsPIN9 by CRISPR/Cas9 technology confers enhanced chilling tolerance in rice [64]. However, whether and how OsPIN9 overexpression regulates rice chilling tolerance is unknown.…”
Section: Introductionmentioning
confidence: 74%
“…These results suggested that IAA and OsPIN genes could affect each other to regulate plant growth and development. PIN is associated with abiotic stress adaptation [33][34][35][36], and abiotic stress treatments influence OsPIN genes' expression. Cold stress inhibited the expression of OsPIN1c, OsPIN1d, OsPIN9, OsPIN10 and OsPIN10b in rice roots, and paralogous OsPIN genes displayed a similar expression profile under cold stress [34], implying that they might act synergistically to modulate rice cold tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…PAT is probably implicated in plant cold adaptation [28]. Recently, we reported that OsPIN9, another auxin efflux carrier, is involved in regulating rice chilling tolerance by modulating ROS homeostasis [33,34]. However, whether OsPIN1b is involved in cold adaptation is still elusive.…”
Section: Mutation Of Ospin1b Substantially Impairs Rice Chilling Tole...mentioning
confidence: 99%
See 2 more Smart Citations